Swift contact tracing can prevent transmission-Case report of an early COVID-19 positive case - Akhil Dhanesh Goel; Pankaj Bhardwaj; Manoj Gupta; Nitesh Kumar; Vidhi Jain; Sanjeev Misra; Suman Saurabh; Mahendra K. Garg; Vijaya L. Nag (Elsevier, 2021)
This is a case study of a positive COVID-19 case who was diagnosed and isolated early on in the infection. However, her seventeen close contacts who were quarantined and under observation remained negative indicating no viable chain of transmission despite high-risk contact. We further discuss the importance of effective contact tracing coupled with strict isolation or quarantine in breaking the chain of transmission.